Sports Tourism Bibliomatrix Analysis In 2023 - Awaloedin, Dipa Teruna; Azzahra, Lintang Salwa; Anjani, Rheka Dwi; Pradini, Gagih; Agustiani, Fitri (CV ODIS, 2023)
Sports Tourism is an outdoor activity that has been around for several years. Spending time watching or practicing certain sports activities does not constitute sports tourism. Not only has an economic impact but also has a social impact on the surrounding community. One of them is the pride of being a champion in our area. Home of sports tourism. In this study, we investigated VoS Viewer and Publish, respectively. Perish (PoP) as an analytical tool in the bibliometrics of sport tourism events. Community-based tourism is the main keyword used in article titles, abstracts, and keywords to get metadata retrieved from the Google Scholar bibliographic database, on Monday, October 16, 2023. The tools used in bibliometric analysis are Microsoft Excel which is used to perform frequency analysis, VoS viewer for data visualization, and Harzing's Publish or Perish, which is used for citation and analysis metrics. This study's results show that most related articles are published in scientific journals, compared to others. Related articles published in scientific journals have obtained the highest citations compared to others. Articles are also found in English. Based on network visualization the most dominant terms (often appear) are